Analisis Pengendalian Kualitas Produk Tahu Menggunakan Statistical Quality Control (SQC): Studi Kasus Pabrik Sumber Gizi - Herlina Lembang Maupak; Yulius Heri Saptomo; Dirarini Sudarwadi (Cakrawala Management Business Journal, 2025)
This study aims to analyze the implementation of product quality control at Sumber Gizi Factory and to identify the factors contributing to product defects using the Statistical Quality Control (SQC) method. The research utilizes production data and defect records from July 2024 to June 2025, with a total output of 365,000 tofu units. Several SQC tools were employed, including check sheets, histograms, Pareto diagrams, p-control charts, fishbone diagrams, and flowcharts. The findings indicate that 4,980 defective units were produced, accounting for 1–2% of the total output. The most frequent defect was uneven size (2,340 units), followed by hard texture and soft texture defects. The p-control chart analysis reveals that the production process is not fully in control, as several data points fall outside the upper and lower control limits. The dominant causes of defects include human factors (worker accuracy), inconsistent production methods, improper measurement of water and coagulant solution, and suboptimal machine pressure. The study recommends improving worker training, standardizing production procedures, and strengthening machine maintenance to enhance process stability and reduce defect rates.